PERANGKAT PEMBELAJARAN MENULIS TEKS EKSPLANASI BERBASIS MODEL PROBLEM BASED LEARNING (STUDI PENGEMBANGAN PADA SISWA KELAS VII SMP NEGERI 8 MAKASAR) - Asdar Asdar (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
Abstract: Writing Learning Tool Model-Based Text explanation Problem Based Learning (Study on the Development of Seventh Grade Students of SMPN 8 Makassar). The purpose of this research was to determine the validity, practicality, and effectiveness of the learning device to write text explanation of Problem Based Learning model based on class VII SMPN 8 Makassar. This study is a research Research and Development (R & D) development model ADDIE. The results obtained in this study were (1) the learning device declared invalid because the criterion of validity has been fulfilled, namely the average value of validity for all aspects of the minimum in the category is quite valid and the validity of every aspect of at least falls under the category valid () (2) the study revealed practically since the criteria of validity are met, namely the overall aspect of the component syntax model of Problem Based learning on the Implementation Plan lesson 1, 2, 3, and 4 are in the category of accomplished entirely (), and (3) the learning device is declared effective because the validity criteria have been met, namely mastery learning outcomes of students = 95%, the average teachers' ability to manage the learning is = 3.7 are in either category (TKG ≤ 3.00 <4.00). Students gave a positive response to the implementation of learning to write explanatory text using the teaching of writing text-based explanatory models of Problem Based Learning = 93.5%.